Human-Centric Functional Modeling of Individual and Collective Biological Systems - Williams, Andy (My University, 2021)
Gaining the capacity to coordinate group research so that from observing the functionality of any system converging on a single best understanding of how that functionality is implemented is reliably achievable, requires a process that is able to analyze that system from a common perspective, such as might be achieved through decomposing that system into a common set of functional components. Human-Centric Functional Modeling provides the potential opportunity to decompose biological systems in this way in order to significantly increase collective ability to derive insight about the behavior of a wide range of biological systems, as well as in order to provide the capacity to derive insights from generalizing an understanding of any one biological systems to any other system or collections of such systems where that understanding might apply. This paper explores the methodology.
Keywords: biomedical engineering; convergence; General Collective Intelligence